PAFc, a Key Player in MLL-rearranged Leukemogenesis - Tan, Jiaying (Impact Journals LLC, 2010)
Recent studies identified an interaction between the Polymerase Associated Factor complex (PAFc) and Mixed Lineage Leukemia (MLL), including MLLrearranged oncoproteins. This interaction is critical for MLL transcriptional activity and MLL-rearranged leukemogenesis. Here, we discuss the potential molecular role of the PAFc in transcriptional dysregulation of MLL target genes and the interplay between PAFc and MLL-rearranged oncoproteins in leukemogenesis.